Pengaruh Madu Apis mellifera Terhadap Pertumbuhan Bakteri Penyebab Penyakit Periodontal (Kajian in Vitro pada Fusobacterium nucleatum) - SUSANTI, Adhe ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Periodontal disease is an inflammatory disease of the supporting tissues of the teeth caused by the formation of plaque with involvement of periodontopathogenic bacteria such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, and others. Prevention and treatment of periodontal disease are began by eliminating the bacterial plaque and reducing the periodontopathogenic bacteria using the antibacterial product such as mouthwash, toothpaste, and irrigation solutions. One of alternative antibacterial compounds that can be used as a base material of mouthwash or irrigation solution is honey. Honey has been extensively researched and known to inhibit the growth of gram-positive and gram-negative bacteria, both aerobic and anaerobic. This study aimed to examine the effect of Apis mellifera honey against bacteria that cause periodontal disease, in vitro studies on Fusobacterium nucleatum. The antibacterial activity of Apis melliferaâs honey was tested by using well diffusion method. Honey was diluted to reach concentration of 20%, 30%, 40%, and 50% and tested against Fusobacterium nucleatum. Sterile distilled water and Chlorhexidine were used as control. Fusobacterium nucleatum were cultured in Muller Hinton Agar (MHA) and incubated with Apis melliferaâshoney for 24 hours at 37o C. The antibacterial activity of Apis melliferaâs honey were seen from the inhibition zone that formed around the wells. The results showed that there were the formation of inhibition zone on concentration of 30%, 40%, and 50%, but no inhibition zone formed at a concentration of 20%. The data of the inhibition zone diameters were analyzed by Shapiro-Wilk test followed by Mann-Whitney test with a significance level of 5%. The conclusion of this study is the Apis melliferaâs honey concentration of 30%, 40% and 50% were able to inhibit the growth of Fusobacterium nucleatum that causes periodontal disease.